The impact of sugarcane burning on hospitalization due to respiratory diseases - Ramos, Dionei [UNESP]; Pestana, Paula Roberta Silva [UNESP]; Trevisan, Iara Buriola [UNESP]; Christofaro, Diego Giulliano Destro [UNESP]; Tacao, Guilherme Yassuyuki [UNESP]; Coripio, Iris Cristina [UNESP]; Ferreira, Aline Duarte [UNESP]; Ramos, Ercy Mara Cipulo [UNESP] (FapUNIFESP (SciELO), 2019)
The scope of this article is to evaluate the impact of emissions from sugarcane burning on hospital admission numbers for respiratory diseases in a sugarcane region. Hospital admission records for respiratory diseases were acquired from the database of the Hospital Information System of the Unified Health System (SIH-SUS) in the period from March 28, 2011 to December 28, 2012. Levels of PM10, NO2, O3, Temperature and Relative Humidity were recorded. Logistic regression models were created to analyze the association between the total number of hospitalizations, atmospheric pollutants and meteorological variables. A total of 1,179 hospitalization admissions were recorded, with a significant increase in cases of pneumonia in the burning period (p = 0.005). Likewise, it was observed that the cluster of PM10 and NO2 was influenced 67.9% (95% CI: 11.111-2.537) followed by cluster PM10, NO2, O3 and Temperature that influenced 91.1% (95% CI: 1.116; 3.271) in the total number of hospitalization admissions. During the sugarcane burning period there were more hospitalization admissions due to respiratory tract diseases, mainly pneumonia, where the influence of air pollutants and temperature in the process of illness in the population was detected.
Impacto da queima da cana-de-açúcar sobre internações hospitalares por doenças respiratórias
Keywords: Air pollutants; Meteorological variables; Pneumonia; Respiratory tract diseases; Sugarcane